Increasing of informational content of serological diagnosis of acute Lyme- borreliosis - M.I. Shkilna; M.A. Andreychyn; O.L. Ivakhiv; I.S. Ischuk; N.A. Nychyk; N.Yu. Vyshnevska; M.M. Korda; I.M. Klishch (Acta Medica Leopoliensia, 2020)
Aim. To improve the serological diagnosis of erythematous form of Lyme borreliosis by detecting antibodies to the Borrelia burgdorferi sensu lato (B. burgdorferi sensu stricto, B. afzelii and B. garinii), using a two-stage diagnostic scheme: ELISA and immunoblot.